2019
DOI: 10.17352/aprc.000035
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary Adenocarcinoma of the lung: Recent updates and literature review

Abstract: Background: Lung cancer is the most frequent cause of cancer-related death worldwide. For adenocarcinomas, histological subtyping is typically performed (e.g. lepidic, acinar, papillary, micropapillary, and solid), as suggested by the World Health Organization. Among these, micropapillary carcinoma has been a focus of signifi cant research in recent years, as it is the newest subtype and has the worst prognosis. Herein, we summarize the most relevant fi ndings of this morphological variant in detail with anecd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Most LADCs are histologically heterogeneous and have a mixed growth pattern. The micropapillary component (MPC) in LADC has been considered as a poor prognostic marker, and even a small proportion of MPC in the primary tumor could contribute to disease progression and recurrence (2)(3)(4). Previous studies have revealed that tumors with MPC have a higher incidence of oncogenic mutations, such as EGFR, KRAS, and BRAF, compared with other histological subtypes (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Most LADCs are histologically heterogeneous and have a mixed growth pattern. The micropapillary component (MPC) in LADC has been considered as a poor prognostic marker, and even a small proportion of MPC in the primary tumor could contribute to disease progression and recurrence (2)(3)(4). Previous studies have revealed that tumors with MPC have a higher incidence of oncogenic mutations, such as EGFR, KRAS, and BRAF, compared with other histological subtypes (5,6).…”
Section: Introductionmentioning
confidence: 99%